OntoM4IS+: Ontology Reuse Method for Information Science - Firmino, Helder Noel Monteiro; Lima, Gercina Ângela (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2018)
Ontologies are a kind of knowledge organisation system (KOS) and it is widely used in many contexts and for different purposes. When the decision of development of a new ontology is taken, the very first decision that is suggested by knowledge specialists, is the possibility of adaptation of existing ontologies. Our intention, with this article, is to propose a new method called OntoM4IS+ (Ontology Reuse Method for Information Science). The main idea is to reuse the content of ontologies or other vocabularies, from multi-sources, as a contribution to the Information Science community in knowledge organisation tasks. We will adopt a hybrid approach, combining the best features of each methodology. The Design Science Research (DSR) will be the support for the whole process. We will use also qualitative research techniques, such as interviews and focus groups to validate our proposal. Moreover, as a research strategy we will follow the bibliographic research technique of published materials. This is a work in progress, and as results is expected a real contribution (the OntoM4IS+ method) to knowledge specialists, as a way to solve the issues arised in the knowledge organisation process.